Aqueous synthesis of glutathione capped ZnSe nanocrystals: synthesis and optical properties. (1st April 2013) - Ding, Y L; Bi, J X; Du, B; Hu, X Y; Liu, F T
Abstract : We have developed an aqueous synthesis for glutathione capped ZnSe nanocrystals. The structure and optical properties of the obtained ZnSe nanocrystals were characterised by X-ray diffraction, dynamic light scattering analysis, TEM, ultraviolet-visible, photoluminescence spectroscopy and Fourier transform infrared spectroscopy. The ZnSe shows a cubic zincblende crystal phase and has a narrow size distribution. Experimental results indicate that the pH value and reaction time play crucial roles in determining optical features. With the pH increasing from 10 to 12, and reaction time from 0 to 2 h, the fluorescence emissions of ZnSe nanocrystals are tuneable between 360 and 405 nm. The high quantum yields are calculated to be in the range of 0·3-22%. Furthermore, the luminescence intensity can be enhanced significantly when the nanocrystal sample is illuminated by room light. The mechanism for the resulting high quality optical properties is also elucidated.